2010
DOI: 10.1111/j.1460-9568.2010.07262.x
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene inhibits the calcium plateau and prevents the development of spontaneous recurrent epileptiform discharges following in vitro status epilepticus

Abstract: Status epilepticus is a clinical emergency that can lead to the development of acquired epilepsy following neuronal injury. Understanding the pathophysiological changes that occur between the injury itself and the expression of epilepsy is important in the development of new therapeutics to prevent epileptogenesis. Currently, no anti-epileptogenic agents exist; thus, the ability to treat an individual immediately after status epilepticus to prevent the ultimate development of epilepsy remains an important clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…We have demonstrated that SE leads to development of Ca 2+ plateau (Raza et al , 2004; Deshpande et al , 2010) that has its origins in Ca 2+ release from intracellular stores (Nagarkatti et al , 2010). To investigate contribution of intracellular CICR receptors in the development of POX Ca 2+ plateau, [Ca 2+ ] i were measured in neurons obtained from POX SE rats in the presence of RyR blocker dantrolene (Nagarkatti et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have demonstrated that SE leads to development of Ca 2+ plateau (Raza et al , 2004; Deshpande et al , 2010) that has its origins in Ca 2+ release from intracellular stores (Nagarkatti et al , 2010). To investigate contribution of intracellular CICR receptors in the development of POX Ca 2+ plateau, [Ca 2+ ] i were measured in neurons obtained from POX SE rats in the presence of RyR blocker dantrolene (Nagarkatti et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate contribution of intracellular CICR receptors in the development of POX Ca 2+ plateau, [Ca 2+ ] i were measured in neurons obtained from POX SE rats in the presence of RyR blocker dantrolene (Nagarkatti et al , 2010). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations